Standard operating procedure for prevention and initial management of COVID-19 in pregnancy at a secondary level hospital in rural South India: a quality improvement project - Johnson, Andrea Daniella; Menezes, Gladys (International Journal Of Community Medicine And Public Health, 2022)
Background: During the COVID-19 pandemic there was an influx of antenatal patients presenting with symptoms while still requiring essential obstetric care. We needed to follow a standard operating procedure (SOP) at this rural maternity hospital for the prevention and initial management of COVID-19 in pregnancy. Methods: An SOP was formulated using national and international guidelines that were tailored to a resource-constrained setting. Healthcare workers were trained to implement the SOP. Sequential Plan-Do-Study-Act (PDSA) cycles enabled fine contouring of the prevention and initial management steps. Data was collected using an observational checklist at the end of each PDSA cycle and compared statistically to the baseline assessments using chi-square test. Results: Patients wearing face mask appropriately increased from 60% to 82.4% (P=0.0007). Patients using hand sanitizer provided at the hospital improved from 50% to 84.8% (P=0.0004). Proportion of patients screened for covid-19 symptoms rose from 74% to 94.4% (P=0.0002). Patients counselled for COVID-19 vaccination increased from 42% to 87.2% (P<0.0001). Proportion of patients triaged at the OPD using the SOP improved from 66.6% to 87.2% (P=0.004). All improvements were statistically significant. Conclusions: The SOP for prevention and the initial management of COVID-19 symptoms in pregnancy was successfully implemented followed by PDSA cycles and can be used in similar health-care settings.